Coffee Consumption Patterns and Anemia Risk: A Cross-Sectional Study of Female University Students in Surakarta - Mahra, Arifa Sofia; Nuhriawangsa, Adi Magna Patriadi; Sari, Yulia (Media Publikasi Cendekia Indonesia, 2025)
Iron deficiency anemia in women of childbearing age is a public health problem. This can be caused by a lack of iron intake from protein sources and impaired iron absorption by inhibitors such as coffee. This study aimed to analyze the relationship between coffee consumption habits and the proportion of protein intake types on the incidence of anemia and menstrual cycle disorders in female university students in Surakarta. This study used a quantitative method with a cross-sectional design. A total of 110 samples were selected through purposive and consecutive sampling. Data collection on coffee consumption habits, protein intake, and menstrual cycle was conducted using questionnaires and SQ-FFQ, while hemoglobin levels were measured using a hematology autoanalyzer; then, it was analyzed using Spearman’s Rank or contingency coefficient test and binary logistic regression. The results showed that 39.1% respondents had anemia and 53.6% respondents had menstrual cycle disorders. Based on multivariate test, the only variable related to the incidence of anemia was the habit of consuming ready-to-drink coffee type (p=0.019; r=3.092). Meanwhile, general coffee consumption habits, specific consumption habits based on frequency and other types, and the proportion of protein intake types were not related to the incidence of anemia (p>0,05). Then, there were no variables of coffee consumption habits and proportion of protein intake types related to menstrual cycle disorders (p>0.05). In conclusion, only the habit of consuming ready-to-drink coffee type significantly increased the risk of anemia.